Comparison of the Morse Fall Scale and STRATIFY scale on the risk of falls among the elderly: DOI: 10.15343/0104-7809.202044311324 - Assis Rodrigues, Josyenne (2020)
The use of risk assessment instruments with an emphasis on preventing an event and reducing damage has providedsupport for the management of falls. The aim of the study was to perform a comparative analysis between the scalesthat predict falls among the elderly Morse Fall Scale (MFS) and St. Thomas Risk Assessment Tool in the Falling ElderlyInpatients (STRATIFY), in a unit of a philanthropic hospital, Campo Grande, MS, Brazil. A quantitative cross-sectionalstudy was carried out from February to September 2018, by nurse residents in the Multiprofessional Health ResidencyProgram, Campo Grande, MS. The STRATIFY and Morse Fall Scale instruments were used. The data were treatedstatistically by the Kolmogorov-Smirnov, Mann-Whitney U and Kruskal-wallis tests. 31 elderly people participated inthe study. The results were heterogeneous in the comparison between the instruments, the MFS demonstrates that asthe patient obtains mobility, the risk for falls increases; while STRATIFY, when investigating risk factors directed to theelderly, identified high levels of high risk for falls in the three assessment moments. It is concluded that the STRATIFYinstrument was significantly associated with the risk of falling and had a better discrimination in predicting falls inhospitalized elderly than MFS.